Multi-country loss rates of honey bee colonies during winter 2016/2017 from the COLOSS survey. Issue 3 (27th May 2018) - Brodschneider, Robert; Gray, Alison; Adjlane, Noureddine; Ballis, Alexis; Brusbardis, Valters; Charrière, Jean-Daniel; Chlebo, Robert; Coffey, Mary F; Dahle, Bjørn; de Graaf, Dirk C; Maja Dražić, Marica; Evans, Garth; et al.
Abstract : In this short note we present comparable loss rates of honey bee colonies during winter 2016/2017 from 27 European countries plus Algeria, Israel and Mexico, obtained with the COLOSS questionnaire. The 14, 813 beekeepers providing valid loss data collectively wintered 425, 762 colonies, and reported 21, 887 (5.1%, 95% confidence interval 5.0–5.3%) colonies with unsolvable queen problems and 60, 227 (14.1%, 95% CI 13.8–14.4%) dead colonies after winter. Additionally we asked for colonies lost due to natural disaster, which made up another 6, 903 colonies (1.6%, 95% CI 1.5–1.7%). This results in an overall loss rate of 20.9% (95% CI 20.6–21.3%) of honey bee colonies during winter 2016/2017, with marked differences among countries. The overall analysis showed that small operations suffered higher losses than larger ones ( p < 0.001). Overall migratory beekeeping had no significant effect on the risk of winter loss, though there was an effect in several countries. A table is presented giving detailed results from 30 countries. A map is also included, showing relative risk of colony winter loss at regional level.